The Effect of Error Propagation on the Performance of Polar Codes Utilizing Successive Cancellation Decoding Algorithm - Gazi, O.; Andi, A. A. (Advanced Electromagnetics, 2019)
In this paper, we discuss and analyze the effect of error propagation on the performance polar codes decoded using the successive cancellation algorithm. We show that error propagation due to erroneous bit decision is a catastrophic issue for the successive cancellation decoding of polar codes. Even a wrong decision on a single bit may cause an abundance of successor bits to be wrongly decoded. Furthermore, we observe that the performance of polar codes is significantly improved if even single bit errors are detected and corrected before the decoding of successor bits.